Diagnostic coronary angiography and percutaneous coronary intervention practices in New Zealand: The All New Zealand Acute Coronary Syndrome-Quality Improvement CathPCI registry 3-year study (ANZACS-QI 37). (1st August 2020) - Wang, Tom Kai Ming; Kasargod, Chethan; Chan, Daniel; Cicovic, Sergej; Dimalapang, Eliazar; Webster, Mark; Nunn, Chris; Devlin, Gerry; El-Jack, Seif; Fisher, Nick; Simmonds, Mark; Kneale, Barry; et al.
Abstract: Background: Coronary heart disease remains one of the leading causes of mortality and morbidity in New Zealand (NZ) and globally. The All New Zealand Acute Coronary Syndrome Quality Improvement (ANZACS-QI) programme includes the CathPCI registry which records all those referred for diagnostic coronary angiography (DCA) and percutaneous coronary intervention (PCI) in NZ. We present the methods and three-years of data from the ANZACS-QI CathPCI registry. Methods: The data was extracted from the ANZACS QI CathPCI registry from 01/09/2014 to 24/09/2017. The ANZACS-QI data dictionary defines all the clinical, procedural and outcomes variables collected, and standard statistical analyses were applied. Results: 40, 870 patients underwent cardiac catheterisation, with a mean age of 65 years, and males making up 67% of the cohort. Indications included acute coronary syndrome 55%, angina with suspected stable coronary disease 28%, valve surgery workup 8%, planned PCI 3%, heart failure/cardiomyopathy 3%, arrhythmia 1% and other 2%. For those undergoing DCA alone, radial access was used in 85% and two-thirds had at least one major artery with >50% stenosis. PCI was performed in 39% of patients. Drug-eluting stents were used in 97%. Conclusion: The CathPCI registry records the characteristics and outcomes of all patients undergoing DCA and PCI in NZ hospitals. As part of the ANZACS-QI programme the registry provides an important platform for quality improvement, research and to inform clinical practice. Highlights: The CathPCI registry records all cardiac catheterisation procedures in New Zealand. It is a platform of ANZACS-QI and its methodology and 3-year practice is reported. There were 43, 097 diagnostic coronary angiograms, with 15, 482 (37%) PCIs. The registry allows quality improvement, research and informs clinical practice.